Analysis of the Plural Pattern of Taksir Based on the Book of Ibn Aqil in the Book of Fathul Qorib (Morphological Study) - Amalia, Fatma; Maulana, Asep (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research aims to make it easier for students or santri to understand more deeply the plural of estimates and their various patterns in the book Fathul Qorib based on the book of Ibn Aqil. This research uses qualitative research methods with the type of library research, namely collecting data through research on books, journals, yellow books and websites. The data analysis used by the researcher was to take data from all the plural words takir in the book of fathul qorib through note-taking media, then group them based on their respective wazans in accordance with the provisions in the book of ibn aqil. The results of the research show that plural estimates based on the pattern of the book of Ibn Aqil contained in the book of Fathul Qorib consist of 184 words consisting of 15 patterns, namely the pattern أَفْعَالٌ: 67 words, pattern فُعُوْلٌ: 32 words, pattern فُعَّالٌ: 3 words, pettern فِعْلَانُ: 2 words, pattern أَفْعِلَاءُ: 3 words, pattern فُعَلَةٌ: 7 words, pattern فُعَلَاءُ: 7 words, pattern فَوَاعِلُ: 10 words, pattern أَفْعِلَةٌ: 7 words, pattern فَعَالِلُ: 4 words, pattern أَفْعُلٌ: 5 words, pattern فِعْلَةٌ: 1 word, pattern فِعَالٌ: 14 words, pattern فُعُلٌ: 3 words, pattern فُعَلٌ: 6 words and pattern فَعَائِلُ: 13 words.